The double-edged sword: Globalization and international Islamic terrorism - Toutounji, Yara (AUC Knowledge Fountain, 2017)
This paper investigates the relationship between globalization and international Islamic terrorism in the modern age of the twenty-first century. It argues that globalization acts as a double-edged sword by both empowering terrorism and, at the same time, international Islamic terrorism is a defensive reaction to the very process of globalization itself. Also, it argues against the dominant Western discourse, which labels Islam as the main cause of international Islamic terrorism by applying a critical discourse analysis that aims at reconstructing the dominant discourse. Along these lines, this work advances that three main underlying sets of popularly held international grievances involving the cultural, economic and political realm, which all feature a common concern with Western hegemony in a new globalized era, are mediated through contemporary religious interpretations of the faith, which work to inspire mobilization and polarization, by Al-Qaeda and ISIS to affect indiscriminate and acute terrorist violence in the international realm.